Analisis Efektivitas Kebijakan Moneter Dalam Perspektif Konvensional dan Syariah Terhadap Inflasi di Indonesia Tahun 2013-2020 - Rindani Dwihapsari; Mega Rachma Kurniaputri; Nurul Huda (Jurnal Ilmiah Ekonomi Islam, 2021)
This scientific research was conducted to see the effect and how the effectiveness of the monetary policy transmission mechanism from both conventional and sharia perspectives to tackle inflation in 2013-2020. The conventional monetary policy transmission mechanism can be seen from the total conventional bank credit (LOAN), the interest rate on Bank Indonesia Certificates (SBI), and the average yield on Government Securities (SUN). Meanwhile, sharia monetary policy can be seen from the yield rates on Bank Indonesia Sharia Certificates (SBIS), total Islamic bank financing (FINC) and the average yield of State Sharia Securities (SBSN). Through the Vector Error Correction Model method, it is found that the SBI results have a significant negative effect so that if the interest rate increases by one percent it will reduce inflation. Unlike the case with the effectiveness as measured by the Impulse Response Function (IFR) and Forecast Error Variance Decomposition (FEVD), where conventional monetary policy is fast in controlling the inflation rate compared to Islamic monetary policy. However, the magnitude of Islamic monetary policy is greater than conventional monetary policy.